'We can't live without beliefs': Self and society in therapeutic engagements - Suvi Salmenniemi (Sage Journals, 2022)
Therapeutic technologies of happiness, emotional wellbeing and self-improvement are a highly
influential cultural phenomenon and a rapidly growing business worldwide; yet little is known of
the motivations for engaging with these technologies. This article addresses this gap by investigating
how therapeutic engagements are experienced and what participants hope to gain from them.
Therapeutic technologies are conceived as psychologically informed regimes of knowledge and
practice which aim to transform one’s relationship to oneself and shape the ways in which one
makes sense of and acts upon oneself and the social world. Drawing on a set of interviews with
consumers of therapeutic technologies in Russia, the article identifies three key motivations for
engaging with such technologies: searching for new blueprints for ethical work on the self after
a profound transformation of the ideological field; coming to terms with new mechanisms of
inequality, particularly in the field of labour; and mobilizing therapeutic technologies as a response
to inadequacies in the field of health. By unpacking these motivations and subjective experiences of
therapeutic engagements, the article seeks to shed light on the growing popularity of therapeutic
technologies under contemporary capitalism.